Sunscreens: potential hazards to environmental and human health - Thomas, Talia; Fat, Marisa; Kearns, Gregory (Frontiers in Marine Science, 2024)
The increasing demand for natural products in the United States reflects a cultural shift towards health and sustainability. This trend infiltrates consumer sectors such as the sunscreen industry, amidst concerns about health and environmental impacts of chemical ingredients. The Hawaii Sunscreen Ban has intensified sunscreen formula safety discussions, particularly regarding butylparaben, oxybenzone, and octinoxate. Even at low concentrations, these compounds bleach hard corals eventually leading to their death. As well, these chemicals pose threats to marine ecosystems and raise concerns about human health, particularly systemic absorption and the possibility of causing endocrine disruption.While some argue for chemical-based sunscreens for skin cancer prevention, others advocate for mineral-based alternatives that avoid harmful ingredients. However, public opinion on sunscreen varies, influenced by adverse reactions, socioeconomic status, gender, and cultural perceptions. Future studies should explore diverse demographic perspectives and long-term health and environmental impacts of products containing potentially toxic ingredients. As well, effective communication strategies to promote sunscreen safety and encourage sustainable sun protection practices is needed.